PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI PADA UPTP KEMENTERIAN KETENAGAKERJAAN RI DI KENDARI - Esty Nurseta; Murdjani Kamaluddin; Alida Palilati (Pascasarjana Universitas Halu Oleo, 2020)
This research aims to examine and explain the effect of organizational culture on employee performance through organizational commitment as a mediating as a mediating variable at the UPTP of Ministry of Manpower in Kendari. The population in this study are all government civil at the UPTP of Ministry of Manpower in Kendari totalling 62 respondents. The sampling technique in this study was carried out by means of the census technique so that the entire population was used as the research sample. Methods oof data collection were used questionnaire. Technique of data anlysis used is Partial Least Square (PLS).The results showed that organizational culture has a positive and significant effect on organizational commitment, organizational commitment has a positive and significant effect on employee performance, organizational culture has a positive and significant effects on employee commitment, and commitment organizational as a partial mediate of the effects organizational culture on employee performance.